N-Acetylcysteine enhances the action of anti-inflammatory drugs as suppressors of prostaglandin production in monocytes. - Hoffer, Erica (2002)
The anti-inflammatory effect of non-steroidal anti-inflammatory drugs (NSAIDs) is associated with inhibition of cyclooxygenase (COX), the rate-limiting enzyme responsible for the synthesis of prostaglandins. Since oxygen free radicals can act as second cellular messengers, especially to modulate the metabolism of arachidonic acid and the prostaglandin tract, it seems plausible that antioxidants might affect the production of prostaglandin by activated cells. This research is focused on the effect of the antioxidant N-acetylcysteine (NAC) on the inhibition of prostaglandin E(2) formation in activated monocytes by specific and non-specific COX inhibitors. We found that lipopolysaccharide-induced prostaglandin E(2) formation was significantly reduced by rofecoxib and by diclofenac, two NSAIDs. Addition of NAC to each of these drugs enhanced the effect of the NSAIDs. These results suggest that one might expect either a potentiation of the anti-inflammatory effect of COX inhibitors by their simultaneous administration with NAC, or obtaining the same anti-inflammatory at lower drug levels.